2005
DOI: 10.1111/j.1742-4658.2005.04907.x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the 13C‐label distribution of the non‐oxidative branch of the pentose phosphate pathway based upon kinetic and genetic evidence

Abstract: During the past decade, 13 C-labeling based metabolic flux analysis (MFA) has increasingly been used to understand the effect of genetic alterations [1,2], changes in external conditions [3,4] and different nutritional regimes [5,6] on the metabolism of micro-organisms. 13 C-labeling based MFA relies on the feeding of 13 C-labeled substrate to a biological system, allowing the labeled carbon atoms to distribute over the metabolic network, and subsequently measuring the 13 C-label distributions of intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 53 publications
2
37
0
Order By: Relevance
“…Metabolic Flux Analysis-Metabolic fluxes were derived using whole isotopologue analysis (15,33). In short, the procedure uses the cumomer balances and cumomer to isotopologue mapping matrices introduced by Wiechert et al (34) to calculate the isotopologue distributions of metabolites in a pre-defined stoichiometric network model for a given flux-set.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic Flux Analysis-Metabolic fluxes were derived using whole isotopologue analysis (15,33). In short, the procedure uses the cumomer balances and cumomer to isotopologue mapping matrices introduced by Wiechert et al (34) to calculate the isotopologue distributions of metabolites in a pre-defined stoichiometric network model for a given flux-set.…”
Section: Methodsmentioning
confidence: 99%
“…Third, the steps catalyzed by transketolase (TK) and transaldolase (TA) in the nonoxidative steps of the PPP are represented in terms of half-reactions to allow for the underlying mechanism of the enzymes and their lack of specificity (Kruger and von Schaewen, 2003;Kleijn et al, 2005;Selivanov et al, 2005). Conventional stoichiometric models of the nonoxidative reactions (Fig.…”
Section: Metabolic Networkmentioning
confidence: 99%
“…3,C and E). Theoretical analysis has shown that this formulation is essential for a correct description of the redistribution of label and that it allows the investigation of parallel pathways supported by different TK isozymes (Kleijn et al, 2005). Accordingly, the halfreaction scheme is used here to maximize the possibility of resolving cytosolic and plastidic contributions to the PPP fluxes.…”
Section: Metabolic Networkmentioning
confidence: 99%
“…These enzymes form a modified pathway, termed the pentose phosphoketolase pathway, in lactic acid bacteria and bifidobacteria (7). This pathway is utilized in the heterofermentative degradation of pentoses and hexoses to the end products CO 2 , ethanol, acetate, and lactate (8). Xfp can convert X5P generated at the end of the oxidative phase of the pentose phosphate pathway to glyceraldehyde 3-phosphate, which can enter the glycolytic pathway, and acetyl phosphate, which Ack can convert to acetate to generate ATP.…”
mentioning
confidence: 99%